The Role of Islamic Social Finance and Covid-19 : Islamic Finance - Haidar, Abdullah; Rusadi, Putri Oktavia (Jurnal Ekonomi Islam, 2024)
This study aims to determine the map of the development of research on the theme of Islamic social finance in the Covid-19 pandemic published by indexed journals. The research was conducted in August 2020. The data analyzed were 47 research publications. The object of study is a published journal published in 2020. The data is then processed and analyzed using the VOSviewer application program to determine bibliometric mapping of the development of Covid-19 research and issues of Islamic social finance. The results of the research show that the number of publications on this theme has increased significantly. The bibliometric visualization shows that the map of the development of Covid-19 research is divided into 4 clusters. Cluster 1 consists of 19 topics, cluster 2 consists of 13 topics, cluster 3 consists of 9 topics, and cluster 4 consists of 8 topics. The finding of this research is that there is special attention to the development of Islamic social finance in order to overcome the impact of the prolonged economic crisis.